A new rooted tree optimization algorithm for indirect power control of wind turbine based on a doubly-fed induction generator. (May 2019) - Benamor, A.; Benchouia, M.T.; Srairi, K.; Benbouzid, M.E.H.
Abstract: A new control strategy based on the root tree optimization (RTO) is presented in order to reduce the chattering phenomena in active and reactive powers, and to minimize the harmonic currents which appear mostly at the level of the rotor side converter (RSC), in a doubly-fed induction generator (DFIG). The root tree optimization is used to adjust the parameters ( K p, K i ) of PI controller (RTO-PI). Simulation results are presented to demonstrate the effectiveness of the new proposed technique. Besides, the system associated with this metaheuristic algorithm can effectively give better dynamic and steady performance. The results with the RTO-PI controller show more performances than the results compared with the classical PI. Highlights: A novel strategy of control based on the root tree optimization is proposed in this paper. This study develops the RTO-PI controller to search optimal PI parameters. RTO-PI strategy is applied to minimize the harmonics currents and chattering phenomenon in the active and reactive powers. Simulation results with RTO-PI technique show more performances than PI technique.